2023
DOI: 10.3390/ijms24010823
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Dependent Mechanisms as a Pharmacological Target for Neuroprotection

Abstract: Modern pharmacotherapy of neurodegenerative diseases is predominantly symptomatic and does not allow vicious circles causing disease development to break. Protein misfolding is considered the most important pathogenetic factor of neurodegenerative diseases. Physiological mechanisms related to the function of chaperones, which contribute to the restoration of native conformation of functionally important proteins, evolved evolutionarily. These mechanisms can be considered promising for pharmacological regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 473 publications
0
4
0
Order By: Relevance
“…This chaperonin serves several functions associated with cell survival, and in particular, it controls the folding and assembly of proteins within the ER and prevents the transport of incorrectly folded proteins/protein subunits [ 22 , 23 ]. Interestingly, among the etiopathogenetic factors of neurodegenerative diseases, the lack of maintenance of protein folding plays a crucial role, therefore suggesting the pharmacological regulation of the chaperones’ function as a therapeutic strategy [ 24 ]. We also demonstrated that all three arms of the UPR are activated by URG7.…”
Section: Discussionmentioning
confidence: 99%
“…This chaperonin serves several functions associated with cell survival, and in particular, it controls the folding and assembly of proteins within the ER and prevents the transport of incorrectly folded proteins/protein subunits [ 22 , 23 ]. Interestingly, among the etiopathogenetic factors of neurodegenerative diseases, the lack of maintenance of protein folding plays a crucial role, therefore suggesting the pharmacological regulation of the chaperones’ function as a therapeutic strategy [ 24 ]. We also demonstrated that all three arms of the UPR are activated by URG7.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence suggests that S1R, in combination with BIP, a regulator of endoplasmic reticulum stress (ERS), plays a pivotal role in the ERS pathway, which is a component of cellular stress and a core mechanism underlying synaptic loss and neurodegeneration in AD pathology ( Ortega-Roldan et al, 2013 ; Venkataraman et al, 2022) . S1R-dependent neuroprotection is likely to be mediated by the regulation of the unfolded protein response (UPR) in ERS ( Voronin et al, 2023) . Under ERS conditions, S1R agonists promote the dissociation of S1R-BIP calcium ion-sensitive chaperone complexes, resulting in enhanced chaperone activity of BIP toward misfolded proteins and S1R binding to client protein IRE1 α .…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory effect of S1R agonists can increase the expression of BIP and brain-derived neurotrophic factor (BDNF) and decrease the expression of pro-inflammatory interleukin-6 (IL-6) ( Hayashi and Su, 2007 ; Rosen et al, 2019 ; Zhemkov et al, 2021) . Thus, S1R agonist regulation presents a viable strategy for the neuroprotective treatment of AD, aimed at reducing ERS and neuroinflammation while enhancing neural plasticity ( Voronin et al, 2023) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPP + has been shown to reduce the expression of BIP in SH-SY5Y cells (Ai et al, 2023), while 6-OHDA has been shown to increase the expression of BIP in neurons (Holtz and O'Malley, 2003). Therefore, more chaperones should be included in studies to discover more effective compounds, such as chaperone PDI and Sigma1R (Perri et al, 2015;Voronin et al, 2023). In addition, the improvement of protein folding by adding chaperones should be verified through more aspects such as electron microscopy observation or structural analysis after protein purification, to increase the convincingness.…”
Section: Increase Of Er's Protein Folding Abilitymentioning
confidence: 99%